Life-long Learning Style of Yangsrisuraj District People in Mahasarakam Province - Somboon, Thongchai (Suan Dusit Graduate School Academic Journal, 2025)
This survey research aimed 1) to study life-long learning style of Yangsrisuraj District people in Mahasarakam Province 2) to study influential factors on life-long education style of those who are habitants of Yangsrisuraj District and 3) to explore the guidelines supporting life-long learning of Yangsrisuraj District people. Samples of 379 people were selected by simple random sampling. Rating scale questionnaire and structured in-depth interview were used as the tool for data collection. Percentage, mean (M) and standard deviation (SD) were employed for data analysis. Research results showed as the follows; 1) the formal lifelong learning aspect of Yangsrisuraj District people in Mahasarakam Province was found at the highest level (X̅ = 4.55, S.D. = 0.48). When considering each aspect, the informal learning and non-formal learning were evaluated at the highest level (X̅ = 4.78, S.D. = 0.33). The informal lifelong learning aspect also showed at the highest level (X̅ = 4.55, SD = 0.48). When considering in terms of items, the item of life-long learning style by self- interest and aptitude was indicated at the highest level (X̅ = 4.88, S.D. = 0.05) which mainly aimed to develop the quality of life 2) There were 3 influential factors on life-long learning style of Yangsrisuraj District people in Mahasarakam Province namely, social factor, economic factor and administrative factor which were indicated at the highest level (X̅ = 4.69, S.D. = 0.31). In this finding, economic factor prominently influenced learning style at the highest level (X̅ = 4.79, S.D. = 0.21) 3) the guidelines supporting life-long learning of Yangsrisuraj District people in Mahasarakam Province consisted of 4 P’s namely 1 Policy 2 Pedagogy 3 Process and 4) Participation.